PEMANFAATAN SUMBERDAYA IKAN DEMERSAL YANG BERKELANJUTAN DI PERAIRAN TEGAL, JAWA TENGAH - Mohammad Imron; John Haluan; M. Fedi A. Sondita; Ari Purbayanto; Daniel R. Monintja (Buletin PSP, 2007)
The demersal fish landing in Indonesia are mostly based on the operation of fishing gear such as trawl, dogol or cantrang, and arad. Even though trawl and the traditional seine nets are very effective but actually they are not selective. Thus, if those gears are not controlled and properly managed, it may impact negatively to demersal fish resources. Consequently, the depletion of demersal fish-stocks may be followed by the reduction of the welfare of fisher community. Therefore, the exploitation of fish resources must be carefully managed particularly for the demersal fish-stock. Formulating the alternative strategies in demersal fishing was the aim of this study. Studies on potency analysis, level of the demersal fishing, biology and economy considerations, and model of demersal fishing in Tegal City were conducted in this study in order to generate a sustainable demersal fisheries.The demersal fish landing in 2005, for rays and sea-snakehead, have exceeded its Maximun Sustainable Yield (MSY) level (more than 100%), i.e. 104.21% and 103.91% respectively. Other demersal fishes have also been categorized as heavily fished (66.8 to 100% of MSY). Based on TAC (80% MSY), most of the landing were approaching TAC value. Therefore, the fishing must be managed to avoid the degradation of demersal fish resource.Indeed, the demersal fisheries has economic beneficiary to the fishers and also to the stakeholders. But, the demersal fisheries have also reached its optimum economic value. Thus, the demersal fishing must be controlled and managed correctly. Financially, the operation of dogol or cantrang was still feasible except for arad.Based on the study, to reassume the sustainable demersal fisheries, the operation of arad and dogol or cantrang must be reorganized. Not only the fishers and the owners, the stakeholders must also be involved in managing the demersal fisheries in Tegal thus any policy taken in the management of demersal fishing could be respected.